2018
DOI: 10.20944/preprints201807.0455.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Expanding Role of Radiosurgery for Brain Metastases

Abstract: Stereotactic radiosurgery (SRS) has become increasingly important in the management of brain metastases due to improving systemic disease control and rising incidence. Initial trials demonstrated SRS with whole brain radiotherapy (WBRT) improved local control rates versus WBRT alone. Concerns with WBRT associated neurocognitive toxicity have contributed to greater use of SRS alone, including for patients with multiple metastases and following surgical resection. Molecular information, targeted agents and immun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Currently, SRS is an established treatment for patients with <4 BMs. 72 [73][74][75] For large lesions not amenable to single-session treatment, staged SRS has shown promise, 76 whereas preliminary studies of re-treated lesions report promising rates of tumor control and side effects. [77][78][79] Finally, new approaches that use metabolic and functional imaging for treatment planning may provide more precise and safe targeting for recurrent treated tumors and those near functional structures such as the corticospinal tracts.…”
Section: Clinical Radiotherapymentioning
confidence: 99%
“…Currently, SRS is an established treatment for patients with <4 BMs. 72 [73][74][75] For large lesions not amenable to single-session treatment, staged SRS has shown promise, 76 whereas preliminary studies of re-treated lesions report promising rates of tumor control and side effects. [77][78][79] Finally, new approaches that use metabolic and functional imaging for treatment planning may provide more precise and safe targeting for recurrent treated tumors and those near functional structures such as the corticospinal tracts.…”
Section: Clinical Radiotherapymentioning
confidence: 99%
“…We read with great interest the paper of Grkovski et al recently published in the European Journal of Nuclear Medicine and Molecular Imaging [1] investigating 18 F-fluorocholine ( 18 F-FCH) PET in patients with progressive brain metastases previously treated by stereotactic radiosurgery (SRS) and scheduled for surgical resection. Previous publications showed that changes in size and enhancement at magnetic resonance imaging (MRI) are not reliable features to distinguish between recurrence and radionecrosis [2][3][4]. In addition, advanced MRI sequences such as perfusion-weighted imaging, diffusion-weighted imaging, spectroscopy, and PET using 18 F-FDG and radiolabeled amino acids can improve the accuracy in this setting [3].…”
Section: Dear Editormentioning
confidence: 99%
“…Yet, iconographic diagnosis remains challenging. Finally, SRS is nowadays used in many centers as an alternative to surgery to treat brain metastases and showed comparable outcome in terms of local control [4,5]. In addition, SRS showed to provide a better control of irradiated metastases compared with whole brain radiotherapy [6] with a lower rate of side effects on neurocognitive function and on quality of life [7].…”
Section: Dear Editormentioning
confidence: 99%